Control of the Flyrock and Vibrations for the Protection of Electrical Installations - Diego Gamarra; Piero Mejía; Jorge Cárdenas (International Society of Explosives Engineers, 2025)
The present case study details the solution to a complex situation in a mining operation, involving the challenge of expanding the tailings storage facility in high-criticality areas adjacent to electrical rooms that provide continuous power to the entire mining process, including water pumping and drainage systems. For this purpose, blasting is required to prepare the construction areas for the new expansion facilities. Upon deciding to proceed with blasting, a comprehensive engineering assessment was conducted to ensure operational continuity without impacting the process, while generating sufficient fracturing in the rock mass to allow extraction with auxiliary equipment. Support from specialists through the Technical Assistance area was requested, and a detailed evaluation was carried out through advanced studies. Field vibration studies were conducted to define attenuation models and characterize the rock mass in the sector. With this information, simulations were carried out using predictive and probabilistic models with Monte Carlo methods to select delay charges and optimal timing for reducing vibration levels and increasing frequency levels. With these measures, the three blasts conducted near the Gas Insulated Substation room, which had distances ranging from 30 to 100 meters, produced the following results: • Vibrations; The three blasts conducted at distances of 100, 30, and 50 meters recorded vibration values of 5.3, 40.2, and 9.5 mm/s, all of which were below the maximum vibration level of 50 mm/s set by the projects area. According to the USBM RI8507-OSMRE standard, all values for Peak Particle Velocity (PPV) and frequency were below the permissible limits. • Flyrock; Through filming and post-blast inspection, it was confirmed that the ejections were within the safety zone. • Fragmentation; The results obtained showed a maximum overbreak size of 1.5 meters, allowing the broken material to be moved effectively.